Cabdio crassus, a new species of cyprinid fish (Teleostei: Cyprinidae) from the Kaladan River of Mizoram, India - Lalramliana, Lalramliana; Lalronunga, Samuel; Singh, Mahender (Zootaxa, 2019)
Cabdio crassus, a new fish species, is described from the Kaladan River in Mizoram, India. The new species is distinguished from all its congeners by having a ventral keel extending from the middle of the chest, between the posterior base of the pectoral fin and along the abdomen up to the anus (vs. more or less keeled median scales from mid-point of abdomen between posterior base of pelvic fin up to anus in all other Cabdio) and 11½–12½ branched anal-fin rays (vs. 7 in C. jaya and 9 in both C. morar and C. ukhrulensis). It is further distinguished from C. morar and C. ukhrulensis by possessing more lateral-line scales (45–51 vs. 38–42 in C. morar and 35–37 in C. ukhrulensis), more predorsal scales (20–23 vs. 17–18 in C. morar and 14 in C. ukhrulensis) and more lateral transverse scales (½7/1/3½ vs. 5/1/2 in both C. morar and C. ukhrulensis). It also differs from C. jaya in having fewer lateral-line scales (45–51 vs. 52–60), more lateral transverse scales (½7/1/3½ vs. 5/1/3) and more pharyngeal tooth-rows (3 vs. 2). Furthermore, the cytochrome c oxidase sub unit I (coi) gene sequence separates Cabdio crassus from all other Cabdio species (interspecies distance ranges from 7.8–12.3%). The anomalies observed among the GenBank sequences of the genus Cabdio are discussed and resolved.